Training Levy-Rebate Incentive Scheme and SME Training Consortium Program to Address Unemployment and Low Productivity in SMEs – A Korean Policy Case - LEE, Kye Woo; SAHU, Dipan Kumar (KDI School of Public Policy and Management, World Bank, 2017)
This case study examines the origin, aims, execution, and achievement of the Small and Medium Enterprises (SMEs) Training Consortium Program in Korea. The success of the Korean government in addressing the issues of low productivity and unemployment in the SME sector stands as an exemplary case for many developing countries. The demand for improved human resources in the growing export-oriented and industrializing Korean economy was effectively achieved by government intervention that promoted an increased role of private players in training markets. These conducive and flexible reforms in the skills development policy, which were brought about in response to the international financial crisis and the changing market needs, caused a structural change in the existing traininglevy incentive system and created an institutional mechanism for SMEs to engage voluntarily and collectively in training their workers. Furthermore, the institutional mechanism effectively addressed the financial and institutional bottlenecks of SMEs in training their workers and the inequitable situation that developed between large enterprises and SMEs in the operation of the workers’ training levy-rebate system.